PENGARUH PENGGUNAAN TEAMS GAMES TOURNAMENTS TERHADAP HASIL BELAJAR IPS SISWA SEKOLAH DASAR - Wira Utami, Rachmawati Hidayah; Marli, Suhardi; Halidjah, Siti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe influence of usage of teams games tournaments on the learning outcomes of social science students grade III Sekolah Dasar Bawamai Pontianak Kota. This study aims to find out how big the influence of using the TGT on the results of IPS learning. The method used in this research is experimental method, with nonequivalen control group design. Collecting technique is measurement technique. Based on result of data analysis, the mean of learning result of student of control class equal to 74,76 while experiment class equal to 78,29. The result of hypothesis test (t-test) using t-test polled variance was obtained tcount of 2,43 and ttable 1,99 (significance level (?) = 5% and dk = 70) showed that tcount is greater than ttable then Ha is accepted. From the calculation of effect size, obtained 0.40 (medium criteria) This means the usage of TGT gives a medium influence on the learning outcomes of students grade III Sekolah Dasar Bawamai Pontianak Kota. Based of researched, admissible (1) teachers in school using varies models like teams games tournaments on social students learning (2) for researcher who shoot for convince knot of teams games tournaments, to create condusif condition on the learning. Keywords: Influence, TGT, Learning Outcomes